Ability of ceramic composite beads as a pre-treatment for laundry wastewater and preparation of the process - Bakar, S A; Nizam, N S M; Musa, S; Mohamed, R M S R; Khamidun, M H; Al-Gheethi, A (2023)
The escalating demand for laundry services, particularly in university districts, has raised concerns about its impact on biodiversity. The situation becomes even more critical when wastewater is discharged into drainage systems without adequate treatment. This study aimed to enhance laundry wastewater treatment by employing ceramic composite beads using ceramic sanitary ware waste and chitosan. The investigation began by characterizing laundry wastewater to identify its specific attributes. Subsequently, the study quantified the removal of zinc as a metal during the laundry wastewater treatment process. Laundry wastewater characteristics were assessed using various parameters, including pH, chemical oxygen demand (COD), total suspended solids (TSS), and turbidity. The result revealed that the treatment of laundry wastewater with ceramic composite beads adsorbent successfully achieved over 50 % reduction in zinc concentration. These findings showed that the ceramic composite bead exhibited an efficiency for metal removal from the laundry wastewater for safe disposal